THE RELATIONSHIP BETWEEN STYLE AND THEME IN A NOVEL (IN THE EXAMPLE OF “THE BELL JAR” BY SYLVIA PATH) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article examines the intrinsic connection between style and theme in Sylvia Plath’s The Bell Jar, illustrating how Plath’s stylistic choices enhance the novel’s exploration of mental illness, societal expectations, and personal identity.The analysis highlights three key aspects of Plath’s style: her use of vivid imagery and metaphor, a confessional tone, and the juxtaposition of beauty and despair. It discusses how these stylistic elements reflect and deepen the novel’s central themes, such as alienation, entrapment, and the struggle for selfhood. The metaphor of the bell jar and the fig tree imagery are emphasized as particularly powerful representations of Esther Greenwood’s internal conflicts. The article concludes by arguing that the interplay of style and theme in The Bell Jar not only enriches the narrative but also demonstrates the profound potential of literary form to evoke emotional and intellectual engagement.